Influence du soutien conditionnel parental perçu sur l'anxiété-trait : rôle du perfectionnisme - Jeremy Pouille; Marine Hascoët (Nantes Université, 2015)
This study contributes to the field of research related to the influence of family practices on the development of anxiety. More specifically, it aims at understanding the relations between trait-anxiety, perfectionism and the perception of a parental conditional support; at school in general, in mathematics, and in arts & crafts. The results of the study conducted on 69 pupils of 5th grade shows that, for girls, the perception of parental conditional support is in a positive relation with trait-anxiety; whatever the subject. This relation is mediatized by a negative perfectionism. Mediation models explain between 40 and 43% of the variance of trait-anxiety.